Higher CO2 Concentrations and Lower Acidic Deposition Have Not Changed Drought Response in Tree Growth But Do Influence iWUE in Hardwood Trees in the Midwestern United States. Issue 12 (13th December 2019) - Maxwell, Justin T.; Harley, Grant L.; Mandra, Tessa E.; Yi, Koong; Kannenberg, Steven A.; Au, Tsun Fung; Robeson, Scott M.; Pederson, Neil; Sauer, Peter E.; Novick, Kimberly A.
Abstract: Several important environmental influences of tree growth and carbon sequestration have changed over the past several decades in eastern North America, specifically, more frequent pluvial conditions, increased carbon dioxide (CO2 ) concentrations, and decreased acidic deposition. These factors could lead to changes in the relationship between tree growth and water availability, and perhaps even decouple the two, having large implications on how future climate change will impact forest productivity and carbon sequestration. Here, we examine the concurrent influence of the climatic water balance (precipitation minus potential evapotranspiration), CO2 concentrations, and sulfate and nitrogen deposition on radial tree growth, carbon isotopes, and intrinsic water‐use efficiency (iWUE) for several hardwood tree species in the Midwestern United States. We found that when considering the simultaneous influence of these factors, the climatic water balance is the dominant influence on annual growth. Therefore, the recent pluvial period is the primary cause of the weakening relationship between radial growth and water availability. Even during pluvial periods, water availability is the primary control on growth, with increasing CO2 concentrations and decreased SO4 deposition being secondary factors. Importantly, the weakening in the climate‐growth relationship is species specific, with Acer species having stable relationships with the climatic water balance, Liriodendron tulipifera showing a strengthening relationship, and Quercus species and Populus grandidentata exhibiting weakening. Thus, interannual variations in soil moisture unevenly impact tree growth and carbon sequestration. Our findings suggest that, despite recent pluvial conditions, increasing CO2 concentrations and decreasing acidic deposition have not buffered the impact of water availability on tree growth and carbon sequestration. Plain Language Summary: In recent decades, many factors that influence tree growth have changed across the Midwestern United States, including more precipitation, higher carbon dioxide concentrations in the atmosphere, and fewer pollutants. Changes in these environmental factors could result in tree growth being less sensitive to water availability. While a weakening relationship between water availability and tree growth is present, it is difficult to determine the cause. Here, we examine the simultaneous influence of a wetter climate, higher carbon dioxide concentrations, and a decrease in pollutants deposition on tree growth and how efficiently trees use water. We found that when considering all three variables, increased moisture was the leading influence on tree growth. Therefore, the recent wet period is behind trees being less sensitive to soil moisture, not increases in carbon dioxide or decreases in pollutants. It is important to note that some species such as oak and aspen did become less sensitive to soil moisture, other species such as maple and tuliptree did not. This is important because when drought conditions return to the region, trees will still be sensitive despite higher carbon dioxide concentrations or decreases in sulfate and nitrate deposition. Key Points: Recent weakening of the relationship between climatic water balance and radial growth and C isotopes was species specific Water availability is the dominant factor influencing long‐term radial growth even when considering the simultaneous influence of other factors such as increasing atmospheric CO2 and decreasing acidic deposition Increasing atmospheric CO2 concentrations increased water‐use efficiency but not growth of most tree species